Characterization of porcine extraembryonic endoderm cells. (21st March 2019) - Shen, Qiao‐Yan; Yu, Shuai; Zhang, Ying; Zhou, Zhe; Zhu, Zhen‐Shuo; Pan, Qin; Lv, Shan; Niu, Hui‐Min; Li, Na; Peng, Sha; Liao, Ming‐zhi; Wang, Hua‐Yan; et al.
Abstract: Objectives: To date, many efforts have been made to establish porcine embryonic stem (pES) cells without success. Extraembryonic endoderm (XEN) cells can self‐renew and differentiate into the visceral endoderm and parietal endoderm. XEN cells are derived from the primitive endoderm of the inner cell mass of blastocysts and may be an intermediate state in cell reprogramming. Materials and methods: Porcine XEN cells (pXENCs) were generated from porcine pluripotent stem cells (pPSCs) and were characterized by RNA sequencing and immunofluorescence analyses. The developmental potential of pXENCs was investigated in chimeric mouse embryos. Results: Porcine XEN cells derived from porcine pPSCs were successfully expanded in N2B27 medium supplemented with bFGF for least 30 passages. RNA sequencing and immunofluorescence analyses showed that pXENCs expressed the murine and canine XEN markers Gata6, Gata4, Sox17 and Pdgfra but not the pluripotent markers Oct4, Sox2 and TE marker Cdx2 . Moreover, these cells contributed to the XEN when injected into four‐cell stage mouse embryos. Supplementation with Chir99021 and SB431542 promoted the pluripotency of the pXENCs. Conclusions: We successfully derived pXENCs and showed that supplementation with Chir99021 and SB431542 confer them with pluripotency. Our results provide a new resource for investigating the reprogramming mechanism of porcine‐induced pluripotent stem cells.